Covering for uncertainty; family as the complex adaptive system in times of polycrisis - Sunil Kumar Raina (Journal of Family Medicine and Primary Care)
Development of a modern healthcare system largely utilising the limited relations model of the west needs an urgent revision . The strength of the Indian and other eastern civilizations has been the central place that family has always occupied in obtaining healthcare. In the emerging era of health polycrisis, nothing offers a more resilient counter to uncertainty than “family”.